2008
DOI: 10.1177/0192623308315827
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Lesions in the Rat Following Administration of an Irreversible Inhibitor of erbB Receptors, Including the Epidermal Growth Factor Receptor

Abstract: CI-1033 (canertinib) is an irreversible inhibitor of the erbB family of transmembrane tyrosine kinase receptors, including the epidermal growth factor (EGF) receptor. Various inhibitors of the EGF receptor, including CI-1033, have resulted in cutaneous toxicity in humans as a common adverse event. In a chronic toxicity study in rats, CI-1033 produced cutaneous lesions with morphologic characteristics similar to that reported in man. Here the authors describe in detail the dermal changes observed, along with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Unfortunately, there is no reliable in vivo model of skin toxicity secondary to the treatment with EGFR inhibitors (60). However, C. Cells were then fixed with 4% paraformaldehyde for 15 minutes and permeabilized with 1% Triton X-100.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no reliable in vivo model of skin toxicity secondary to the treatment with EGFR inhibitors (60). However, C. Cells were then fixed with 4% paraformaldehyde for 15 minutes and permeabilized with 1% Triton X-100.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation of the cutaneous adnexa in rodents can occur in association with dermatophytosis (see 'Common skin diseases of laboratory rodents') or as a sequel of topical or systemic treatment with chemicals. ( 80 Mecklenburg, 2009; 16 Brown et al, 2008)…”
Section: Nomenclaturementioning
confidence: 99%
“…Moreover, animal studies conducting in rats and dogs revealed that no additional toxicities occur except for the known EGFR inhibitor-related events. [15][16][17][18] The objective of this multicenter, open-label, phase 1 trial was to evaluate the safety, tolerability, efficacy, and pharmacokinetics (PKs) of almonertinib in patients with locally advanced or metastatic NSCLC positive for EGFR mutation who had been previously treated with firstor second-generation EGFR TKIs.…”
Section: Introductionmentioning
confidence: 99%